2018
DOI: 10.1029/2018gl080125
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Distributions of Dayside ECH Waves Observed by MMS

Abstract: Strong electrostatic electron cyclotron harmonic (ECH) waves on the dayside magnetosphere have been reported based on observations of the Magnetospheric Multiscale (MMS) spacecraft. In this study, we analyze high‐quality wave data from the four MMS satellites between 1 September 2015 and 30 August 2018 to investigate the statistical properties of dayside ECH emissions. The results show that dayside ECH waves are preferentially observed on the prenoon side in the outer magnetosphere (L = 8–12), with average wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 45 publications
3
31
0
Order By: Relevance
“…To determine terrestrial dayside ECH waves in the fundamental band, Lou et al. (2018) implemented that the ratio between the maximum intensity in the frequency range of f ce − 2 f ce and the intensity at f ce should be over 5. To determine Saturnian ECH waves in this study, the ratio between the maximum and minimum wave intensity in the frequency range of n f ce − ( n + 1) f ce is set above 1.25 in order that Saturnian ECH waves can be identified reliably…”
Section: Instrumentation and Databasementioning
confidence: 99%
See 2 more Smart Citations
“…To determine terrestrial dayside ECH waves in the fundamental band, Lou et al. (2018) implemented that the ratio between the maximum intensity in the frequency range of f ce − 2 f ce and the intensity at f ce should be over 5. To determine Saturnian ECH waves in this study, the ratio between the maximum and minimum wave intensity in the frequency range of n f ce − ( n + 1) f ce is set above 1.25 in order that Saturnian ECH waves can be identified reliably…”
Section: Instrumentation and Databasementioning
confidence: 99%
“…To minimize the impacts of Saturn's E rings and of the background noise, the data with r < 4.4 R s are excluded. Since the spectral densities of |MLAT| > 40° are disturbed by Z-mode waves and Saturn kilometer radio (SKR), and ECH waves are hardly observed in the region of |MLAT| > 40°, only the observation data with the radial distance to the Saturn's center 4.4 R s < r < 10 R s and |MLAT| ≤ 40° are selected for analyses (2) To determine terrestrial dayside ECH waves in the fundamental band, Lou et al (2018) implemented that the ratio between the maximum intensity in the frequency range of f ce − 2 f ce and the intensity at f ce should be over 5. To determine Saturnian ECH waves in this study, the ratio between the maximum and minimum wave intensity in the frequency range of n f ce − (n + 1) f ce is set above 1.25 in order that Saturnian ECH waves can be identified reliably Over-13-year Cassini RPWS observations (Gurnett et al, 2004) provide an unprecedented opportunity to investigate in detail ECH wave events and their distribution features in Saturn's magnetosphere.…”
Section: Instrumentation and Databasementioning
confidence: 99%
See 1 more Smart Citation
“…The dayside ECH waves are preferentially observed at the prenoon side in the equatorial region of the outer magnetosphere ( L=812) with electric field amplitude >0.1 mV/m. In addition, due to the off‐equatorial magnetic field minimum, dayside ECH waves can be also found at higher magnetic latitudes ( 15<false|MLATfalse|<40) with a moderate occurrence rate of 30% and wave amplitude of >0.1 mV/m (Lou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The statistical analysis of ECH waves using Time History of Events and Macroscale Interactions during Substorms data by Ni et al () shows that ECH waves occur throughout the outer magnetosphere ( L > 5), and expand to higher L ‐shells with enhanced occurrences when geomagnetic activity intensifies. Using the data from the Magnetospheric Multiscale spacecraft, Lou et al () have found double peaks of ECH wave occurrence zone on the dayside and high occurrence rates of prenoon ECH waves. They further propose that dayside ECH waves can potentially contribute to the formation of dayside diffuse aurora.…”
Section: Introductionmentioning
confidence: 99%